S48 Air Pollution Particulate Matter Promotes Dc Maturation And Enhances Their Stimulation Of Cd8 Lymphocyte Responses. (10th November 2014) - Ho, TR; Pfeffer, PE; Mann, E; Kelly, FJ; Matthews, NC; Hawrylowicz, CM
Abstract : Background: High levels of ambient urban particulate matter (UPM), a component of air pollution, are associated with respiratory tract infections and exacerbations of airways diseases. Dendritic cells (DCs) exposed to inhaled UPM orchestrate the resulting immune response. We have previously shown that UPM-stimulation of DCs results in enhanced proliferation of naïve CD4 lymphocytes but decreased priming of IFNγ-producing CD4 lymphocytes. These CD4 lymphocytes are important in anti-viral immune responses; however, Tc1 CD8 lymphocytes have more direct anti-viral action. In this research we have studied the effect of UPM on DC priming of CD8 lymphocytes. Methods: CD1c peripheral blood DCs were isolated, cultured in the presence/absence of UPM stimulation, with GM-CSF or in medium alone. DC expression of CD83, CCR7, CD40 and MHC Class I were measured by flow-cytometry at 24 h. Pre-treated DCs were also cultured with naïve CD8 lymphocytes in an allogeneic mixed-lymphocyte reaction (MLR). Lymphocyte proliferation (flow-cytometric measurement of CFSE) and cytokine production (multiplex bead array) were assessed at day 5. The proportion of lymphocytes primed to produce IFNγ was measured at day 7 (intracellular staining). Results: UPM-stimulation increased DC expression of the maturation marker CD83 (p = 0.0038) and chemokine receptor CCR7 (p = 0.0018). It had no effect on CD40 or MHC Class I expression. UPM-stimulation of DCs also significantly increased CD8 lymphocyte proliferation (p = 0.020), and the production of IFNγ, TNFα and IL-13 by CD8 lymphocytes in MLR at day 5 (all p < 0.05; Table 1 ). The proportion of CD8 lymphocytes primed to produce IFNγ was also increased by UPM-stimulation of DCs (p = 0.034). Conclusion: No evidence of an impaired Tc1 response was seen with UPM-stimulated DCs, in contrast to our previous findings with CD4 T lymphocytes. This may be because CD8 lymphocytes are more primed to respond and produce cytokines at baseline. However, UPM-treatment of DCs did significantly increase DC expression of CCR7, which directs DCs to lymph nodes, and increased the priming of Tc1 and Tc2 responses in the absence of any other stimulation. Inhalation of UPM may give rise to pathological CD8 responses to otherwise innocuous novel antigens.